External Body Scores in Male Sakub Sheep Based on Different Physiological Age - Meliana, Denis Agita; Agustinah Setyaningrum; Akhmad Sodiq; Agus Susanto (Faculty of Animal Science, Jenderal Soedirman University in associate with the Animal Scientist Society of Indonesia (ISPI) and the Indonesian Association of Nutrition and Feed Science (AINI), 2024)
This study aims to determine the external body score, including body condition score (BCS), body fat percentage (BFP), plumpness index (PI), and body conformation index (BCI), of male Sakub sheep at different physiological ages (lambs vs rams). The research was conducted from October to December 2023 in Pandansari Village, Paguyangan District, and Wanareja Village, Sirampog District, Brebes Regency, Central Java. The data were collected following purposive random sampling procedure and the Nomograph Harry King formula of which 118 male Sakub sheep (59 lambs and 59 rams) were sampled. The data were analyzed using the chi-square test to determine suitability or differences in each category and parameter. The results showed that the average values for lambs and rams are as follows: (1) body condition score of 3 ± 0.59 and 3.5 ± 0.50, (2) body fat percentage of 13.72 ± 2.55 and 15.94 ± 2.22, (3) plumpness index of 0.87 ± 0.02 and 0.88 ± 0.01, and (4) body conformation index of 0.29 ± 0.02 and 0.30 ± 0.01. It can be concluded that rams possess superior body condition and fat reserves, which may reflect their advanced physiological development and greater muscle mass relative to younger animals. This information is critical for optimizing management strategies in Sakub sheep production, particularly in breeding and selection programs aimed at enhancing productivity and carcass quality. Further research is warranted to explore the genetic and environmental factors influencing these traits.